Simultaneous Oscillations at Two Unrelated Frequencies - Jones, N.B. (My University, 1965)
This thesis is principally concerned with the conditions under which a feedback oscillator with a single non-linear element can support two component waves, These component waves are required to have unrelated frequencies. A theory is produced to predict the oscillation frequencies and amplitudes and examine their stability. The conclusions reached in this thesis are then compared with those reached by previous workers in the same field. The concluding parts of the thesis contain an examination of the possible approximations which can be made in order to represent various non-linear elements mathematically and also a demonstration of a system for examining frequency relationships without recourse to direct numerical measurement.
Keywords: feedback, oscillator,single non-linear element, waves, frequencies, amplitude